NEED ASSESMENT PENGEMBANGAN MEDIA PEMBELAJARAN TENIS LAPANGAN BERBASIS APLIKASI THUNKABLE - Septian Raibowo; Tono Sugihartono; Andes Permadi; Aldino Aldino; Miftah Fajrin Rahmi (Jurnal Muara Pendidikan, 2023)
The purpose of this study is to evaluate the necessity for creating thunkable applications-based tennis learning medium. By completing a questionnaire, a survey is used in this research method. 140 students from the semester I and III physical education study programs participated in the study as respondents. The findings of this study demonstrate that tennis is a required course that must be taken, that 92.85% of students lack the necessary tennis skills, that free internet connection is provided in every campus room, that 100% of students own computers and smartphones, and that 60% of students are freshmen. The sole learning resources remain secondary economics and instructors. The findings of this analysis show that the creation of tennis learning media based on thunkable applications is actually required in order to achieve the learning objectives.